Students' reflective journaling: an impactful strategy that informs instructional practices in an EFL writing university context in Qatar. Issue 4 (4th July 2019) - Ahmed, Abdelhamid M.
ABSTRACT: Reflective journals are used in the literature to promote students' learning, develop writing skills, assess students' reflection level, promote teachers' professional development, and gather research data. However, the current research bridges the gap in the literature by exploring the impact of students' reflective journals on informing instructional practices in an EFL writing context at a university in Qatar. Informed by Gibb's reflective cycle (1988) (i.e. description, feelings, evaluation, conclusion and action) and social constructionism, the researcher developed a reflective journal to help students reflect on the instructional practices. Using a case study methodology, the researcher collected seventy-eight reflective journals, written by bilingual female university students in Qatar. Data was analysed qualitatively using thematic content analysis. Findings revealed that students preferred the following teaching strategies: gradual teaching, exemplification, discussion, comprehension checking, cooperative learning, and graphic organisers. Findings also showed students' reported challenges such as strict classroom management, lack of teacher's electronic feedback, teacher's frequent questioning, recurrent turn-taking, time mismanagement, lack of handouts, cooperative learning problems, mocking students, ringing mobile phones, unpunctual students and dealing with disruptive students. Implications for instructional practices are provided.